Binding of TATA Binding Protein to a Naturally Positioned Nucleosome Is Facilitated by Histone Acetylation - Sewack, Gerald F. (American Society for Microbiology, 2001)
The TATA sequence of the human, estrogen-responsive pS2 promoter is complexed in vivo with a rotationally and translationally positioned nucleosome (NUC T). Using a chromatin immunoprecipitation assay, we demonstrate that TATA binding protein (TBP) does not detectably interact with this genomic binding site in MCF-7 cells in the absence of transcriptional stimuli. Estrogen stimulation of these cells results in hyperacetylation of both histones H3 and H4 within the pS2 chromatin encompassing NUC T and the TATA sequence. Concurrently, TBP becomes associated with the pS2 promoter region. The relationship between histone hyperacetylation and the binding of TBP was assayed in vitro using an in vivo-assembled nucleosomal array over the pS2 promoter. With chromatin in its basal state, the binding of TBP to the pS2 TATA sequence at the edge of NUC T was severely restricted, consistent with our in vivo data. Acetylation of the core histones facilitated the binding of TBP to this nucleosomal TATA sequence. Therefore, we demonstrate that one specific, functional consequence of induced histone acetylation at a native promoter is the alleviation of nucleosome-mediated repression of the binding of TBP. Our data support a fundamental role for histone acetylation at genomic promoters in transcriptional activation by nuclear receptors and provide a general mechanism for rapid and reversible transcriptional activation from a chromatin template.